Essential Domain-Dependent Roles Within Soluble IgG for in vivo Superantigen Properties of Staphylococcal Protein A: Resolving the B-Cell Superantigen Paradox - Ulloa-Morales, Alejandro J.; Goodyear, Carl S.; Silverman, Gregg J. (Frontiers in Immunology, 2018)
Staphylococcus aureus is a common commensal and frequent opportunistic pathogen that causes invasive infections that often recur. Co-evolution with the host has led to the development of toxins that affect diverse immune cell types. Recent reports have highlighted the contributions of staphylococcal protein A (SpA). This small oligomeric secreted protein contains 4-5 homologous domains with two distinct immunoglobulin-binding sites; one for IgG Fc domains, while a separate site binds an evolutionarily conserved surface on Fab encoded by VHIII clan related genes. The Fab-binding site has been implicated in in vivo supraclonal VHIII-BCR targeted B-cell depletion by an activation induced death pathway. Yet the concept of a superantigen for B lymphocytes poses a seeming paradox. Unlike TCR that are expressed only in a membrane-associated form, BCR are expressed in both a membrane BCR form and in secreted Ig forms, which permeate virtually every part of the body at high levels. We therefore asked, why circulating immunoglobulin do not block the superantigen properties of SpA? Herein, we show that soluble IgG molecules are not in vivo inhibitors of these B-cell superantigen effects but are instead essential for potentiating these properties. We also show that the Fc subclass of circulating IgG is an indirect critical determinant of the B-cell superantigen effect. In contrast, host FcgR and complement are not required for SpA mediated in vivo B-cell depletion. Unexpected, after VHIII-IgG2a pretreatment SpA challenge resulted in fatal anaphylactic reactions, which we speculate may have involved FcgR interactions with mast cells and basophils. Cumulatively, our findings illuminate a cunning and potent molecular strategy by which a bacterial toxin effectively confounds the contributions of host B-lymphocytes to immune defenses.